Adaptive responses to flooding in wild rice species with various genomes other than AA. (3rd July 2022) - Sasayama, Daisuke; Niikawa, Mayuko; Hatanaka, Tomoko; Fukayama, Hiroshi; Azuma, Tetsushi
ABSTRACT: In the present study, 15 accessions of wild rice species belonging to genome groups different from that of Oryza sativa were tested for their adaptive response to flooding at the seedling and mature stages. Under complete submergence at the seedling stage, reduced underwater shoot elongation and high survival rate after the recovery period were observed in the accessions of O. minuta as well as tetraploid O. punctata, O. eichingeri, O. officinalis, O. alta, O. grandiglumis, O. latifolia, and O. australiensis . This suggests that these species exhibit submergence tolerance at the seedling stage. During gradual submergence at mature stage, promoted internodal elongation was observed in the accessions of diploid and tetraploid O. punctata, O. alta, O. grandiglumis, O. latifolia, and O. brachyantha . This suggests that these species possess floating ability. Remarkably, two CCDD genome species, namely O. grandiglumis and O. latifolia, strongly displayed both submergence tolerance at the seedling stage and floating ability at mature stage, suggesting that these species are valuable genetic resources for improving rice adaptability to flooding. SUB1A and SNORKEL genes are known to confer submergence tolerance and floating ability to O. sativa, respectively. However, SUB1A, SNORKEL1, and SNORKEL2 genes were not detected in any of the wild rice accessions investigated in the present study. Our results suggest that adaptive responses to flooding in the investigated wild rice species can be achieved independently of the presence or absence of SUB1A and SNORKEL genes. GRAPHICAL ABSTRACT: uf0001